An Overlooked Pathway in 1, 3‐Dipolar Cycloadditions of Diazoalkanes with Enamines. Issue 12 (3rd February 2022) - Li, Le; Mayer, Peter; Stephenson, David S.; Ofial, Armin R.; Mayer, Robert J.; Mayr, Herbert
Abstract: Methyl diazoacetate reacts with 1‐( N ‐pyrrolidino)cycloalkenes to give products of 1, 3‐dipolar cycloadditions and azo couplings. The kinetics and mechanisms of these reactions were investigated by NMR spectroscopy and DFT calculations. Orthogonal π‐systems in the 1, 3‐dipoles of the propargyl‐allenyl type allow for two separate reaction pathways for the (3+2)‐cycloadditions. The commonly considered concerted pathway is rationalized by the interaction of the enamine HOMO with LUMO+1, the lowest unoccupied orbital of the heteropropargyl anion fragment of methyl diazoacetate. We show that HOMO/LUMO(π*N=N ) interactions between enamines and methyl diazoacetate open a previously unrecognized reaction path for stepwise cycloadditions through zwitterionic intermediates with barriers approximately 40 kJ mol −1 lower in energy in CHCl3 (DFT calculations) than for the concerted path. Abstract : The most popular illustration of the role of Frontier Molecular Orbitals (FMO) in 1, 3‐dipolar cycloadditions must be revised: the reactions of diazoacetates with enamines proceed stepwise and are controlled by interactions of the enamines' HOMO with π*N=N (LUMO) and not with the unoccupied orbital of the heteropropargyl fragment (LUMO+1). Tautomers of the intermediate zwitterions have been observed and the mechanism studied by DFT computations.